THE EFFECT OF USING CONCRETE MEDIA ON STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING - Azizah; Rika Setiawati, Ni Made (Tadulako Social Science and Humaniora Journal, 2023)
This study aims to determine the effect of the use of Concrete Object Media on Student Learning Outcomes in Science Learning Class II SD Inpres 2 Kotaraya. The method used is a quasi experiment with the equivalent pretest-posttest design. The population in this study amounted to 28 students with a sample of 28 students. Sampling technique by means of saturated sampling. Class II A at Inpres 2 Kotaraya as the experimental class and class II B at Inpres 3 Kotaraya Elementary School as the control class. The learning outcome instrument is a multiple choice test that has been validated. Based on the results of the posttest given to the experimental and control classes, the average value of the control class pretest was 64.21 and the experimental class pretest was 61.35. The average posttest value in the control class was 73.85 and the experimental class was 88.78. The average value of the experimental posttest has increased from the average value of the pretest and this is reinforced by the results of the hypothesis test. Based on the results of the final hypothesis test, it was found that the significant value was 0.000 because the significant value obtained was <0.05, so Ho was rejected and Ha was accepted. The results showed that there was an effect of using concrete objects media on student learning outcomes in science learning Class II SD Inpres 2 Kotaraya.